THE IMPORTANCE OF INNOVATIVE PEDAGOGY IN PRIMARY EDUCATION - Yoldasheva Roila Jumaevna,; Royobova Shakhlo Anvar kizi, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
Innovative pedagogy has become a central focus in modern primary education as global societies move toward creativity-driven, technology-enhanced learning environments. This article explores the conceptual foundations, significance, and practical applications of innovative pedagogical approaches for young learners. It examines how child-centered methods, digital tools, collaborative learning, and inquiry-based techniques foster critical thinking, motivation, and long-term academic success. Furthermore, the paper discusses the role of teachers, curriculum designers, and educational policy in supporting innovation.